Human rights in the robot age: challenges arising from the use of robotics, artificial intelligence, and virtual and augmented reality - van Est, Rinie; Gerritsen, Joost (The Hague, 2017)
"Smart devices surveilling our lives. Artificial intelligence technologies steering our behaviour. Care robots hindering human contact. Does this sound terrifying? Inevitable? It does not have to be. Time for a wakeupcall. The report demonstrates that these technologies can have a positive or a negative impact on human rights. Regarding these rights, we focus on issues relating to the right to respect private life, human dignity, ownership, safety and liability, freedom of expression and the prohibition of discrimination as well as access to justice and the right to a fair trial. The Rathenau Instituut conducted this research on the invitation of the Committee on Culture, Science, Education and Media of the Parliamentary Assembly of the Council of Europe (PACE). Our research shows that the human rights framework forms a practical starting point for policy makers tasked with regulating robotics, artificial intelligence or similar technologies. However, in certain cases clarification on the rights is needed. We therefore argue in favour of two, novel, human rights: the right to not be measured, analysed or coached, and the right to meaningful human contact."